Influence Of Corporate Governance On Financial Performance Of Companies - Nur Lely Sofia; Indira Januarti (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2022)
The main objective of this study is to determine the effect of the proportion of independent commissioners, audit committees, directors' remuneration, institutional ownership, public ownership and foreign ownership on the company's financial performance. The number of research samples is 248 observations. The analytical method used is the Partial Least Square (PLS) method. The results showed that the variables of the proportion of independent commissioners, directors' remuneration and foreign ownership had a positive effect on financial performance, while the audit committee, institutional ownership and public ownership had no effect on the company's financial performance.